Bulletin 46 An Investigation of Explosion-Proof Motors - H. H. Clark (The National Institute for Occupational Safety and Health (NIOSH), 1912)
The term "explosion-proof," as applied by the Bureau of Mines to an electric motor, refers to a motor inclosed by a casing so constructed that an explosion of a mixture of mine gas (methane) and air within the casing will not ignite a mixture of the same gas surrounding the motor. There are two classes of motors so constructed: First, a totally inclosed class built strong enough to withstand high internal pressures and so designed that the efficiency of all inclosing covers can be satisfactorily maintained; second, a class provided with relief openings or valves designed to relieve the pressure of an explosion within the motor casing and to cool any products of combustion dis- charged through the valves. A satisfactory motor of the first class is much more expensive to build than an equally safe motor of the second class. For this rea- son, attempts to make motors explosion-proof have been confined chiefly to motors of the second class.